A novel dual-tone molecular glass resist based on adamantane derivatives for electron beam lithography. Issue 26 (24th June 2022) - Hu, Shengwen; Chen, Jinping; Yu, Tianjun; Zeng, Yi; Wang, Shuangqing; Guo, Xudong; Yang, Guoqiang; Li, Yi
Abstract : A novel dual-tone molecular glass (AD-10Boc) resist was developed for electron beam lithography. The AD-10Boc resist can resolve dense line patterns of 21 nm and 30 nm L/S for negative-tone and positive-tone development, respectively. Abstract : A novel molecular glass compound (AD-10Boc) based on adamantane derivatives was synthesized and characterized. The thermal analysis indicated that a glass transition temperature ( T g ) of 80.6 °C and a thermal decomposition temperature ( T d ) up to 150 °C were observed. The X-ray diffraction analysis of the powder of AD-10Boc suggests that it exists in an amorphous state at room temperature. The good thermal resistance and film-forming performance of AD-10Boc suggest that it is a candidate for resist materials. AD-10Boc resist was produced by mixing it with minor components of photo-acid generator and other additives. The AD-10Boc resist was demonstrated as a dual-tone (positive and negative tone) resist for electron beam lithography. By optimizing the lithographic performance, the AD-10Boc resist can resolve dense line patterns of 21 nm L/S at 50 μC cm −2 and 30 nm L/S at 100 μC cm −2 for negative-tone and positive-tone development, respectively. This study provides a new example of a dual-tone molecular glass resist fulfilling most of the requirements of EBL.